تخطيط قلب الجنين أثناء المخاض - يوسف, أحمد; النقري, محمد; عبود, علي (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة في قسم التوليد وأمراض النساء في مشفى الأسد الجامعي باللاذقية خلال العام ( 2005 - 2006 ). وتضمنت (121) ماخضا" أجري لهن تخطيط قلب جنين أثناء المخاض وتحليل معطيات التخطيط مع التركيز على النمط القافز وتقييم أبغار الوليد بالدقيقة الأولى والدقيقة الخامسة بعد الولادة وإجراء عيارات (Be – Pco2 – Po2 –PH) للحبل السري. وكانت النتائج على الشكل الآتي: الأكثر سوءاً بالنسبة لحالة الجنين هو ظهور DIPIV على تخطيط قلب الجنين حيث كان متوسط PH الشريان السري (7.14±0.05) يليه DIPII حيث كان متوسط PH الشريان السري (7.17±0.08) يليه النمط القافز حيث كان متوسط PH الشريان السري (7.23±0.05) وDIPIII حيث كان متوسط PH الشريان السري (7.23±0.07). ترافق النمط القافز و DIPIII مع التفاف الحبل السري بنسبة ( 57.1%), (42.9%) على الترتيب مقابل (13.4%) في التخطيط السليم. The study was performed in Obstetrics and Gynecology Department, ALAssad University Hospital in Lattakia during the year (2005-2006), and included 121 parturient women. Electronic fetal monitoring during labor, Apgar score in 1st and 5th minute, and titrating (PH – Po2 – Pco2 – Be) from umbilical cord were performed The study concludes that the most harmful pattern for fetal being is the appearance of DIPIV on the fetal monitoring charts. The PH average for umbilical artery was (7.14±0.05), followed by DIPII with the average PH for umbilical artery (7.17±0.08) and DIPIII with PH (7.23±0.07). Saltatory pattern and DIPIII were conjugated with umbilical artery compression with (57.1%), (42.9%) respectively, in contrast with normal chart (13.4%).